Marketing Strategy Analysis for Polytechnic Innovation Products: A Case Study of Flagship Products in Indonesian Polytechnics - Akbar, Taufik; Sugianingsih, Ni Made Widhi (KnE Social Sciences, 2024)
This research aims to analyze effective marketing strategies for innovative products from five state polytechnics in Indonesia. The research method employed a qualitative approach with data collection techniques involving in-depth interviews and document analysis, involving 20 respondents from various backgrounds, including polytechnic employees, students, business practitioners, and alumni. The data analysis was conducted using descriptive analysis and content analysis methods. The research findings indicate that the current marketing strategies for polytechnic innovation products are primarily limited to promotion through social media and polytechnic websites. The recommendations from this study include steps to enhance more effective marketing strategies. The first recommendation is to conduct market research to identify potential target markets. Subsequently, develop products that align with market needs, establish competitive pricing, and select appropriate distribution channels. Furthermore, the study suggests that successful marketing strategies require support from polytechnic management and trained human resources in marketing. Polytechnics should also build partnerships with industry and government agencies to expand their market reach and enhance the branding of their innovative products. Lastly, the research recommendations underscore the importance of using social media for innovative product promotion, strengthening collaboration with the industry, and optimizing available funds to expand the reach of polytechnic innovation product promotion. By implementing these recommendations, polytechnics can enhance the effectiveness of their marketing strategies and contribute to the success of marketing their flagship products from the five state polytechnics in Indonesia. Keywords: strategy, marketing, product, innovation, polytechnic